MANAGEMENT CULTURE AS A FACTOR OF ENTERPRISE DEVELOPMENT IN THE CONDITIONS OF MODERN CHALLENGES AND WORLD CHANGES - Tyukhtenko, N.A. (The actual problems of regional economy development, 2023)
The article is aimed at researching the management culture of enterprises as an important factor in its development under the influence of modern challenges, world and domestic trends. The author's understanding of the concept of "management culture" as a system from the point of view of increasing the adaptability of the enterprise's activities on the basis of leadership, development (self-development), and innovation. It is aimed at the formation of a general organizational culture, capable of substantiating a set of measures of managerial influence (social, economic, organizational, motivational, psychological, emotional, etc.) on a team of employees (followers) for the implementation of current and strategic tasks in the conditions of modern challenges and changes. Reasoned interdependence of the state and trends of domestic and world development (based on the analysis of modern world models VUCA, VUCA-Prime, BANI) on management and management culture, features of the content of management culture under the influence of changes are shown. The importance of the category "educated leadership" in the context of modern transformations and the content of managerial culture is proven. Educated leadership itself correlates, from our point of view, with the applied principles of modern management culture. The importance of human-centeredness, socio-psychological, emotional, adaptive factors of modern management and managerial culture is emphasized. The influence of the technological revolutions of Industry 4.0 and Industry 5.0 on the development of management culture from the point of view of increasing the efficiency of the country, region, industry, enterprise, taking into account demographic, ecological, digitalization trends, the transformative impact of digital technologies and changes in existing business models is shown. In order to speed up the process of Ukraine's accession to the European Union, the relevance of increasing the meaningfulness of management culture to solve the problems formed by the European Commission in the context of the implementation of Industry 5.0 is substantiated: the creation of Government 5.0; implementation of corporate governance 5.0; ensuring vertical and horizontal coordination and synergy.